RESEARCH ON THE INTERCONNECTION OF THE MINOR RIVER BED WITH THE RIPARIAN AREA (PANGEEA, 2025)
The morphology of the minor bed is influenced by a number of natural and anthropogenic factors. The shape of the minor bed is conditioned by the geological structure and hydrological and hydraulic parameters of the flow. The minor river bed, in general, has a continuous morphological transformation of a natural type. The research carried out on three types of beds taken from the mountain area (Tazlăul Sărat River), hill (Moldova River) and plain (Bahlui River) highlighted the increasingly strong influence of anthropogenic factors on the morphology of the minor bed. The presence of economic facilities in the riparian zone influences the morphological change of the minor river bed. The research also followed the evolution of the minor bed in interconnection with the riparian zone. Morphological anthropogenic transformations generated by human and economic requirements appear on river sections.
Keywords: shape; morphology; natural factors; anthropogenic factors